The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acscatal.0c04179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhodium Modification on Activity of Platinum Nanoparticle-Loaded Carbon Catalysts for Electrochemical Toluene Hydrogenation

Abstract: Toluene (TL)/methylcyclohexane (MCH) is an attractive organic hydride couple for secure storage and transportation of large amounts of hydrogen. Electrochemical hydrogenation of TL to MCH can achieve energy savings compared with hydrogenation using molecular hydrogen generated separately, and catalyst development to improve the kinetics of electrochemical TL hydrogenation is imperative. Here, we found that using rhodium to modify Pt nanoparticles (NPs) supported on carbon black (Pt/C) significantly improved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…To check whether Cu adatoms are completely exchanged with Rh atoms in the present galvanic replacement conditions, the amount of Rh substituted for Cu adatoms deposited at an E upd of 0.35 V was quantified by atomic absorption spectroscopy according to the previous Rh quantification method . Consequently, it was determined as 1.8 nmol cm –2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To check whether Cu adatoms are completely exchanged with Rh atoms in the present galvanic replacement conditions, the amount of Rh substituted for Cu adatoms deposited at an E upd of 0.35 V was quantified by atomic absorption spectroscopy according to the previous Rh quantification method . Consequently, it was determined as 1.8 nmol cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…62,63 To check whether Cu adatoms are completely exchanged with Rh atoms in the present galvanic replacement conditions, the amount of Rh substituted for Cu adatoms deposited at an E upd of 0.35 V was quantified by atomic absorption spectroscopy according to the previous Rh quantification method. 54 Consequently, it was determined as 1.8 nmol cm −2 . Since the amount of Cu adatoms evaluated from the charge for Cu-upd was 2.7 nmol cm −2 , the mole ratio of the replaced Rh to Cu adatoms is 2/3, indicating that the Cu adatoms on the Pt electrode were quantitatively replaced with rhodium.…”
Section: Evaluation Of Ecsa For Polycrystalline Pt and Rhmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Subsequently, H ads are added to unsaturated bonds (e. g., C=C) or consumed through hydrogen evolution reaction (HER) path. [9][10][11] The key to improve ECH performance is to intensify the adsorption of unsaturated chemical bonds on catalyst surface as well as weaken the PdÀ H binding to facilitate H ads transfer and addition to substrate. Previous studies have indicated that tensile strain could upshift the d-band center to intensify the species adsorption (e. g., C=C) to speed up ECH.…”
Section: Introductionmentioning
confidence: 99%